2009
DOI: 10.1074/jbc.m109.033316
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Mutational Analysis of YtvA from Bacillus subtilis

Abstract: LOV2 domains (1), members of the superfamily of PAS domains (2, 3), are abundant in all domains of life and were first identified in plant phototropins (4). These photoreceptors regulate stomatal opening, phototropism, etc. and contain two N-terminal LOV domains that confer light regulation on the C-terminal Ser/Thr kinase domain (4). They also occur in bacteria, in which YtvA from Bacillus subtilis has been best characterized (for a review, see e.g. Ref. 5). Its N-terminal LOV domain binds FMN and shows the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…One possible interpretation of these data was that oxygen levels in the medium were influenced by the population cell density, and that this variable might influence the sensitivity to blue light, since other studies have reported that light can lead to the generation of reactive oxygen species (ROS) (25,35). To investigate this hypothesis, we measured the inhibitory effect of blue light on cells grown in BHI medium containing the ROS scavenger dimethylthiourea (DMTU).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible interpretation of these data was that oxygen levels in the medium were influenced by the population cell density, and that this variable might influence the sensitivity to blue light, since other studies have reported that light can lead to the generation of reactive oxygen species (ROS) (25,35). To investigate this hypothesis, we measured the inhibitory effect of blue light on cells grown in BHI medium containing the ROS scavenger dimethylthiourea (DMTU).…”
Section: Resultsmentioning
confidence: 99%
“…A deletion mutant, ⌬lmo0799, and a missense mutant with an alanine replacing the conserved cysteine at position 56 of the Lmo0799 protein (C56A) were constructed. The lmo0799 C56A mutant was constructed to genetically test the idea that this residue is essential for the light-sensing function of the protein, as proposed by others (20,21,35). Two phenotypes known to be associated with the loss of Lmo0799 function were tested: derepressed motility in the presence of light and loss of ring formation in response to light-dark cycles (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…The percent quench varied from 19 (for GTP) and 49% for GDP (Table 2). These data suggest a nucleotide interaction surface in Rv1739C STAS that directly or indirectly perturbs Trp 50 and/or the three Tyr residues through conformational effects on adjacent or interposed residues.…”
Section: Guanine Nucleotide Binding By Rv1739c Stasmentioning
confidence: 97%
“…4A, Rv1739c STAS was photolabeled by a ␥-biotinylated derivative of 8-N 3 -GTP, and this photolabeling was prevented in the presence of excess unlabeled GTP. The presence of a unique Trp residue, Trp 50 (aa 486 of Rv1739c holoprotein), in Rv1739c STAS and Tyr residues at STAS positions 7, 19, and 21 ( Fig. 3E and supplemental Fig.…”
Section: Guanine Nucleotide Binding By Rv1739c Stasmentioning
confidence: 99%
See 1 more Smart Citation